Penerapan Metode Think Pair Share (TPS) untuk Meningkatkan Self-Efficacy dan Hasil Belajar Matematika Siswa Kelas VII A MTs Nurul Karim NW Kebon Ayu - Fahrozi Fahrozi; I Ketut Sukarma; Yuntawati Yuntawati (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
Abstract : The aim of this research is to improve self-efficacy and mathematics learning outcomes using the Think Pair Share Type Cooperative Method in Class VII A MTs Nurul Karim NW Kebon Ayu. This research is classroom action research (Action Research). The flow of activities for each cycle consists of 4 (four) components, namely: action plan (plan), implementation of action (action), observation and evaluation (observation/evaluation), and reflection (reflection). The approach used in this research is a qualitative approach and a quantitative approach. This research was carried out in semester 2 at MTs Nurul Karim NW Kebun Ayu. The subjects in this research were class VIIA students with 21 students including 13 male students and 8 female students. The research instruments used were questionnaires, observations and learning outcomes tests. Data collection techniques in this research are questionnaires, observation of test results and documentation. Data analysis in this research is self-efficacy, learning outcomes and observation. The results of the research showed that there was an increase in the percentage of student learning completeness from 42.85% in cycle I to 80.95% in cycle II, which means they had achieved classical indicators of success. Meanwhile, self-efficacy increased from the sufficient category in cycle I to the good category in cycle II. So it can be concluded that this research is said to be successful. Keywords: Learning outcomes, Self-Efficacy, Think Pair Share (TPS